2007
DOI: 10.1002/ajmg.a.31599
|View full text |Cite
|
Sign up to set email alerts
|

Matthew‐Wood syndrome: Report of two new cases supporting autosomal recessive inheritance and exclusion of FGF10 and FGFR2

Abstract: We describe two fetal cases of microphthalmia/anophthalmia, pulmonary agenesis, and diaphragmatic defect. This rare association is known as Matthew-Wood syndrome (MWS; MIM 601186) or by the acronym "PMD" (Pulmonary agenesis, Microphthalmia, Diaphragmatic defect). Fewer than ten pre- and perinatal diagnoses of Matthew-Wood syndrome have been described to date. The cause is unknown, and the mode of transmission remains unclear. Most cases have been reported as isolated and sporadic, although recurrence among sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Recent results from our and other groups have demonstrated the expression of both FGF10 and ISL1 in a region probably corresponding to a second heart field in human embryos at appropriate and similar stages of morphogenesis [11], [37]. A non-exhaustive bioinformatics analysis of the FGF10 locus to search for putative highly conserved ISL1 consensus binding sites with the sequence YTAATGR, using rVista 2.0 (http://rvista.dcode.org) [39] and the ECR browser (http://ecrbrowser.dcode.org) [40], identified two candidate regions conserved among therian mammals (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Recent results from our and other groups have demonstrated the expression of both FGF10 and ISL1 in a region probably corresponding to a second heart field in human embryos at appropriate and similar stages of morphogenesis [11], [37]. A non-exhaustive bioinformatics analysis of the FGF10 locus to search for putative highly conserved ISL1 consensus binding sites with the sequence YTAATGR, using rVista 2.0 (http://rvista.dcode.org) [39] and the ECR browser (http://ecrbrowser.dcode.org) [40], identified two candidate regions conserved among therian mammals (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…Based on the murine phenotypes of Fgf10 and Fgfr2-IIIb knockouts and their expression patterns [3], [19], we had previously found very similar expression during normal human embryonic development; however, sequencing of both FGF10 and FGFR2-IIIb in human fetuses exhibiting great vessel defects that resembled those in knockout mice, among other symptoms, did not demonstrate coding mutations [37]. The responsible gene turned out to encode a protein, STRA6, necessary to bring vitamin A into cells, a first step in transcriptional regulation through retinoic acid receptor binding [63], [64].…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, work in humans has demonstrated that mutations in the Fgfr2 coding region are associated with duodenal stenosis. 65 Work in mice has demonstrated that mutations in a number of members of the Hedgehog signaling pathway genes ( Gli-1, Gli-2, Gli-3, Ihh , and Foxf1 ) do not result in intestinal atresias but in some cases can cause variations in imperforate anus. 63,66 These results suggest that formation of atresias may require disruptions of other signaling cascades in addition to the Hedgehog pathway.…”
Section: A New Round Of Questionsmentioning
confidence: 99%
“…These two malformations have been described together with pulmonary agenesis in the Matthew-Wood syndrome [MWS; OMIM 601186; Berkenstadt et al, 1999]. P ulmonary hypoplasia/agenesis, D iaphragmatic hernia/eventration, A nophthalmia/microphthalmia, and C ardiac defects, or PDAC syndrome, overlaps with MWS [for selected recent reports, see Ceylaner et al, 2006; Li et al, 2006; Chitayat et al, 2007; Martinovic-Bouriel et al, 2007]. Recently mutations in the STRA6 gene were identified in a phenotype that overlaps with both MWS and PDAC [Golzio et al, 2007; Pasutto et al, 2007], with clinical features of affected families comprising pulmonary agenesis, diaphragmatic defects, anophthalmia or severe microphthalmia, cardiac defects, pancreatic malformations and intrauterine growth retardation.…”
Section: To the Editormentioning
confidence: 99%